Factors influencing medical student self‐competence to provide weight management services. Issue 1 (24th October 2018) - Doshi, R. S.; Gudzune, K. A.; Dyrbye, L. N.; Dovidio, J. F.; Burke, S. E.; White, R. O.; Perry, S.; Yeazel, M.; van Ryn, M.; Phelan, S. M.
Summary: This study aimed to identify factors associated with high obesity care self‐competence among US medical students. The authors performed a cross‐sectional analysis of 2014 survey data on fourth year medical students collected online as part of the Medical Student Cognitive Habits and Growth Evaluation Study (CHANGES). Independent variables included quality and quantity of interaction with patients and peers with obesity; hours of communication and partnership skills training; negative remarks against patients with obesity by supervising physicians, and witnessed discrimination against patients with obesity. The dependent variable was self‐competence in providing obesity care. Of 5823 students invited to participate, 3689 (63%) responded and were included in our analyses. Most students were white (65%), half were women and 42% had high self‐competence in caring for patients with obesity. Factors associated with high self‐competence included increased interaction with peers with obesity (39% vs. 49%, P < 0.001) and increased partnership skills training (32% vs. 61%, P < 0.001). Increased partnership skills training and quantity of interactions with peers with obesity were associated with high student self‐competence in providing obesity‐related care to patients. Medical schools might consider increasing partnership skills training to improve students' preparedness and skill in performing obesity‐related care.